2017
DOI: 10.5897/ajest2016.2248
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of soils and some water sources on the Western Flank of Mount Cameroon

Abstract: Human activities such as agriculture, construction of houses and automobile workshops and natural processes alter the properties of soils and water which affect the health of plants, animals and humans. This work was therefore, aimed at investigating some physicochemical properties of soils and some water sources on the Eastern Flank of Mount Cameroon with altitude and selected natural and/or anthropogenic activities. Soils and water were sampled in February 2010 and analysed for their physicochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Although some plants can thrive under varying pH conditions, the optimum pH for most agricultural soils range from 5.5 to 7.5 (Köpp et al, 2011). The acidic nature of the studied soils is in agreement with soil survey studies carried out in the Western Flank of Mt Cameroon by Fomenky et al, (2017). The results of this study are also similar to those of Orock and Lambi, (2014) who showed that the soils in the wetland milieu around these study sites that were used for the cultivation of Colocasia esculenta were slightly acidic.…”
Section: Soil Phsupporting
confidence: 91%
“…Although some plants can thrive under varying pH conditions, the optimum pH for most agricultural soils range from 5.5 to 7.5 (Köpp et al, 2011). The acidic nature of the studied soils is in agreement with soil survey studies carried out in the Western Flank of Mt Cameroon by Fomenky et al, (2017). The results of this study are also similar to those of Orock and Lambi, (2014) who showed that the soils in the wetland milieu around these study sites that were used for the cultivation of Colocasia esculenta were slightly acidic.…”
Section: Soil Phsupporting
confidence: 91%
“…The mean monthly air temperature ranges from 19˚C -30˚C, and soil temperature at 10 cm depth decreases from 25˚C to 15˚C. The soil is derived from weathered volcanic rocks dominated by silt and clay [25] [26] [27].…”
Section: Description Of Experimental Sitementioning
confidence: 99%
“…With an anticipated 889,800 tons of production and a 9.4% yearly growth rate, Cameroon is ranked as Africa's fifth-largest tomato producer (Tolly and Kamtchouing, 2016). Tomato is grown in Cameroon's third, fourth, and fifth agro-ecological zones (Kirui and Abiodun, 2017) due to their favorable climatic and edaphic factors (Norbert et al, 2017). Nonetheless, tomato production in some cities like Kumba in the meme division of the fourth agro-ecological zone is challenging (Kimengsi and Tosam, 2013).…”
Section: Introductionmentioning
confidence: 99%